Aged xCT-Deficient Mice Are Less Susceptible for Lactacystin-, but Not 1-Methyl-4-Phenyl-1,2,3,6- Tetrahydropyridine-, Induced Degeneration of the Nigrostriatal Pathway - Bentea, Eduard; De Pauw, Laura; Verbruggen, Lise; Winfrey, Lila C.; Deneyer, Lauren; Moore, Cynthia; Albertini, Giulia; Sato, Hideyo; Van Eeckhaut, Ann; Meshul, Charles K.; Massie, Ann (Frontiers in Cellular Neuroscience, 2021)
The astrocytic cystine/glutamate antiporter system xc- (with xCT as the specific subunit) imports cystine in exchange for glutamate and has been shown to interact with multiple pathways in the brain that are dysregulated in age-related neurological disorders, including glutamate homeostasis, redox balance, and neuroinflammation. In the current study, we investigated the effect of genetic xCT deletion on lactacystin (LAC)- and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced degeneration of the nigrostriatal pathway, as models for Parkinson’s disease (PD). Dopaminergic neurons of adult xCT knock-out mice (xCT-/-) demonstrated an equal susceptibility to intranigral injection of the proteasome inhibitor LAC, as their wild-type (xCT+/+) littermates. Contrary to adult mice, aged xCT-/- mice showed a significant decrease in LAC-induced degeneration of nigral dopaminergic neurons, depletion of striatal dopamine (DA) and neuroinflammatory reaction, compared to age-matched xCT+/+ littermates. Given this age-related protection, we further investigated the sensitivity of aged xCT-/- mice to chronic and progressive MPTP treatment. However, in accordance with our previous observations in adult mice (Bentea E., Sconce M. D., Churchill M. J., et al. Neurosci Lett. 2015, 593:1-6), xCT deletion did not confer protection against MPTP-induced nigrostriatal degeneration in aged mice. We observed an increased loss of nigral dopaminergic neurons, but equal striatal DA denervation, in MPTP-treated aged xCT-/- mice when compared to age-matched xCT+/+ littermates. To conclude, we reveal age-related protection against proteasome inhibition-induced nigrostriatal degeneration in xCT-/- mice, while xCT deletion failed to protect nigral dopaminergic neurons of aged mice against MPTP-induced toxicity. Our findings thereby provide new insights into the role of system xc- in mechanisms of dopaminergic cell loss and its interaction with aging.